(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
The length-weight relationships and reproductive biology of Synodontis nigrita was studied. Fish specimens were collected from fishermen catch at the landing site. Estimated exponent (b) varied between 1.949 and 2.845 (2.3092±0.08). Correlation (0.915±0.01) between length and weight indicated a strong positive relationship. There were more females than males in the fish species, the difference was not significant (P>0.05). Male fish recorded gonadosomatic index range from 0.253±0.03 to 2.715±0.15 and 0.410±0.05 to 5.352±0.72 for females. The gonadosomatic index of the male fish was not significantly different from that of the female. Rainy months gonadosomatic index were significantly higher than the dry months (P<0.05). The fish was observed to exhibit negative allometric growth. The species investigated recorded higher values of GSI in the wet season indicating the breeding period of the fish.